Theoretical model for the hydraulic properties of geosynthetic drainage materials. Issue 2 (April 2012) - Gourc, J.P.; Giroud, J.P.; Aubert, V.
Abstract : ABSTRACT: This technical note presents a theoretical model for laminar and non-laminar flow through porous media. The relationship between hydraulic conductivity and hydraulic gradient expressed by the model is in good agreement with the results of hydraulic conductivity tests. The model provides a means to rigorously extend (by interpolation and extrapolation) the results of tests giving the hydraulic characteristics of porous media, such as the results of hydraulic transmissivity tests on geonets. A numerical example, based on actual test results, is presented.